The Arrival of Fast Internet and Employment in Africa - Comment - David Roodman (Institute for Replication (I4R), 2024)
Hjort and Poulsen (2019) frames the staggered arrival of submarine Internet cables on the shores of Africa circa 2010 as a difference-in-differences natural experiment. The paper finds positive impacts of broadband on individual- and firm-level employment and nighttime light emissions. These results largely are not robust to alternative ge-ocoding of survey locations, to correcting for a satellite changeover at end-2009, and to revisiting a definition of the treated zone that has no clear technological basis, is narrower than the spatial resolution of nearly all the data sources, and is empirically suboptimal as a representation of the geography of broadband.
https://doi.org/10.7910/DVN/V7ASIP
Keywords: 330